2014
DOI: 10.1186/2047-9158-3-19
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in transthyretin amyloidosis therapy

Abstract: Mutant (MT) forms of transthyretin (TTR) cause the most common type of autosomal-dominant hereditary systemic amyloidosis—familial amyloidotic polyneuropathy (FAP). Until 20 years ago, FAP was thought to be an endemic disease, but FAP is known to occur worldwide. To date, more than 130 mutations in the TTR gene have been reported. Genotype-phenotype correlations are seen in FAP, and some variation in clinical presentation is often observed in individual kindreds with the same mutation and even among family mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
118
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(120 citation statements)
references
References 114 publications
(135 reference statements)
1
118
0
1
Order By: Relevance
“…Although FAP was thought to be restricted to an endemic presence in specific areas, especially Portugal, Sweden, and Japan, progress in biochemical and molecular genetic analyses has shown that it is present throughout the world and more than 130 mutations in the TTR gene have been reported. 4 The treatments are liver transplantation and new drugs (diflunisal and tafamidis) to stabilize TTR, 13 which are usually effective. The median survival exceeds 20 years; 14 the reported 5-year survival rate is 92%.…”
Section: Figure 3 a 36-year-old Man With Familial Amyloid Polyneuropmentioning
confidence: 99%
“…Although FAP was thought to be restricted to an endemic presence in specific areas, especially Portugal, Sweden, and Japan, progress in biochemical and molecular genetic analyses has shown that it is present throughout the world and more than 130 mutations in the TTR gene have been reported. 4 The treatments are liver transplantation and new drugs (diflunisal and tafamidis) to stabilize TTR, 13 which are usually effective. The median survival exceeds 20 years; 14 the reported 5-year survival rate is 92%.…”
Section: Figure 3 a 36-year-old Man With Familial Amyloid Polyneuropmentioning
confidence: 99%
“…Tafamidis has been approved in Europe, Japan, Mexico, and Argentina, but only for the treatment of early-stage FAP. 2,36) However, tafamidis was unable to halt the progression of the disease in patients with advanced FAP caused by the V30M mutation. 37) Therefore, the development of other drugs is of great importance for the treatment of ATTR.…”
Section: Drugs For Attrmentioning
confidence: 99%
“…Clinical trials have been conducted to assess the efficacy of diflunisal on the progression of ATTR. 2,3,5) In addition, a new drug, tafamidis, has been developed for the treatment of FAP. Tafamidis binds with high affinity to the T4-binding pockets of the TTR tetramer, leading to stabilization of the tetramer and inhibition of the amyloidogenesis 35) (Fig.…”
Section: Drugs For Attrmentioning
confidence: 99%
See 2 more Smart Citations